The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1109/te.2015.2427116
|View full text |Cite
|
Sign up to set email alerts
|

Recommender System and Web 2.0 Tools to Enhance a Blended Learning Model

Abstract: Blended learning models that combine face-to-face and online learning are of great importance in modern higher education. However, their development should be in line with the recent changes in e-learning that emphasize a student-centered approach and use tools available on the Web to support the learning process. This paper presents research on implementing a contemporary blended learning model within the e-course "Hypermedia Supported Education". The blended model developed combines a learning management sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 20 publications
(31 reference statements)
2
49
0
3
Order By: Relevance
“…The study of Artino and Stephens (2009) mentioned that the design of teaching strategies should be based on learners' motivations and beliefs in such an environment. Learners' different online learning self-efficacy levels mean different needs, which requires the flexibility of learning design and personalized supports, which is in line with Hoic et al (2016). For example, according to the level of self-efficacy, learners could be assigned different roles in learning, and different learning activities should be recommended to different learners due to their self-efficacy.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The study of Artino and Stephens (2009) mentioned that the design of teaching strategies should be based on learners' motivations and beliefs in such an environment. Learners' different online learning self-efficacy levels mean different needs, which requires the flexibility of learning design and personalized supports, which is in line with Hoic et al (2016). For example, according to the level of self-efficacy, learners could be assigned different roles in learning, and different learning activities should be recommended to different learners due to their self-efficacy.…”
Section: Resultsmentioning
confidence: 98%
“…Some researchers who have attempted to add Web2.0 tools such as Wiki pages, Google Docs and Facebook into learning (Wang, 2016;Abodoli et al, 2015;Hoic, Dlab, & Mornar, 2016)have found that these tools can assist teaching and improve learning outcomes (Alexander, 2006;Boulos, Maramba, & Wheeler, 2006). This study attempts to combine collaborative learning with Web2.0 tools to create a new learning approach called online collaborative learning.…”
Section: Introductionmentioning
confidence: 99%
“…The system recommends optional e-tivities, possible collaborators, Web 2.0 tools, and provides advice regarding the level of participation [10], [11]. Using the ELARS web applica-tion [12] teachers define course learning design with all planned activities and criteria for determining recommendations while students enter their preferences, read recommendations and choose among the recommended items.…”
Section: Educational Recommender System Elarsmentioning
confidence: 99%
“…The following characteristics are represented as continuous variables with values ranging from -1 to 1 [10]: preferences of Web 2.0 tools and VARK learning styles (determined using questionnaires), knowledge level (calculated based on test results), and activity level (calculated based on activity data retrieved from Web 2.0 tools). The student model also contains two characteristics with nominal values: gender and program of study.…”
Section: Educational Recommender System Elarsmentioning
confidence: 99%
“…Since the initial thought of blended learning is combination of classroom teaching and e-learning, but some research suggested to enlarge the definition by combination of not only the classroom and network environments, but also various technologies, various pedagogies and so on [3,8,9]. So, as the general model, we take the classroom and network as environment factors, and the emphasis of blended learning model is the combination of all kinds of teaching elements, teaching strategies, teaching activities and so on, and selection of environments between classroom and network in order to take good advantage of the merits of classroom teaching and network learning.…”
Section: General Model Of Blended Learningmentioning
confidence: 99%